Titanium dioxide for color master batch with low FPV value as well as preparation method and application of titanium dioxide
By covering the boroughite-type hydrated alumina layer on the surface of the titanium dioxide and performing organic surface treatment, the problems of poor dispersion of titanium dioxide in the masterbatch and unstable melting filtration pressure are solved, and better dispersion and melting are achieved performance reduces production costs.
Patent Information
- Application Number
- CN202411481650.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-20
AI Technical Summary
The existing titanium dioxide has poor dispersion and unstable structure in masterbatches, resulting in unstable melt filtration pressure, affecting the quality and production cost of plastic products.
By coating the rutile titanium dioxide with uniform 5-8 nanometer hydrated alumina layer on the surface of rutile titanium dioxide and grafting it with organic surface treatment agent, titanium dioxide with good dispersion was prepared, and a specific process flow includes beating, Sand milling, ultrasonic dispersion, hydrolysis and airflow crushing are used to form stable titanium dioxide.
It effectively reduces the FPV value of the masterbatch, improves the dispersion and melt filtration performance of titanium dioxide in the masterbatch, meets high-end production needs, reduces production costs, and improves the performance stability of plastic products.
Smart Images

Figure CN119161639A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of titanium dioxide, in particular to titanium dioxide for low FPV value masterbatch and a preparation method and application thereof. Background Art
[0002] Masterbatches are increasingly used in plastics, and the quality requirements for white masterbatches, in particular, are becoming increasingly stringent. Besides the quality of the resin, titanium dioxide plays a crucial role in influencing the quality of white masterbatches. Titanium dioxide has specific performance specifications for use in masterbatches, chemical fibers, and plastics. Titanium dioxide is a key white pigment in white masterbatches, effectively scattering visible light and imparting whiteness, brightness, and opacity. Processability is also a key consideration, leading to high requirements for the pigment volume concentration (PV) and melt filter pressure value (FPV) of titanium dioxide in masterbatches.
[0003] The FPV value is an important indicator for judging the dispersion of titanium dioxide in the masterbatch during the melt production process of plastic products. The smaller the FPV value, the better the melt filtration stability and the better the dispersion of titanium dioxide in the masterbatch. The better the dispersion, the more uniform the film formation or injection molding of the plastic product, which effectively improves product quality and reduces production costs.
[0004] Masterbatch raw materials contain titanium dioxide. Nano-titanium dioxide has a high surface energy and contains polar hydroxyl groups on its surface. Therefore, nano-titanium dioxide is prone to agglomeration due to polar adsorption or moisture absorption. Therefore, when titanium dioxide is added as an additive to raw materials for the production of plastics, etc., there is a problem of uneven dispersion of titanium dioxide in the raw materials.
[0005] Pigment dispersibility is a key performance indicator, crucial for the coloring of plastic products. Dispersibility, also known as grind dispersibility or grind wettability, refers to the ability of a pigment to disperse in the medium being colored. Generally speaking, the better the pigment's dispersibility, the higher its tinting strength and hiding power, resulting in a more uniform and delicate appearance, less speckling, and minimal color variation in the colored product. Oil absorption is a physical value that indicates the relationship between pigment powder and vehicle. It not only describes the mixing ratio, wettability, and dispersibility of the pigment powder and vehicle, but also influences the coating's formulation and various physical properties after film formation. A pigment with lower oil absorption is more likely to disperse, wet, and fill the medium.
[0006] CN116515323A discloses a high-performance titanium dioxide pigment comprising a titanium dioxide base material, the titanium dioxide base material being coated with a silicon oxide coating layer, the silicon oxide coating layer being coated with an aluminum oxide coating layer, and the aluminum oxide coating layer being coated with an organic coating layer. The titanium dioxide base material is composed of a mixture of two unsurface-treated chloride-process rutile titanium dioxide semi-finished products; the silicon oxide coating layer is produced by reacting the titanium dioxide base material with a silicate solution; the aluminum oxide coating layer is produced by reacting the silicon oxide coating layer with an aluminate solution; and the organic coating layer is produced by reacting the silicon oxide coating layer with an organic treatment agent, wherein the organic treatment agent is a polyol and / or organosilicon. Although this technical solution has good color space values and plastic filtration pressure values, it requires two coating layers to wrap the outer titanium dioxide layer, which places high demands on the processing technology.
[0007] CN117024992A discloses a method for producing a highly dispersible, low-oil-absorption titanium dioxide powder. The method employs a two-stage grinding process, where the titanium dioxide slurry is ground twice, swirl-fed, and then subjected to an inorganic coating. The method also employs a concurrent coating method using aluminum sulfate and liquid caustic soda, with the pH of the slurry maintained between 4.0 and 5.0. After the inorganic coating is completed, the slurry undergoes three washes and drying, followed by an organic coating. The method aims to alter the deposition pattern of aluminum hydroxide in an acidic environment, converting it into an amorphous aluminum hydroxide coating on the titanium dioxide surface. However, amorphous aluminum hydroxide has poor thermal stability and high adsorption capacity. However, due to its lack of a clear crystal structure, amorphous aluminum hydroxide exhibits poor thermal stability and is prone to decomposition when heated or exposed to heat. This easily destroys the surface structure during melt extrusion with resins such as polyethylene, resulting in a loss of optimal performance in the final masterbatch.
[0008] Based on the above-mentioned existing technology, there are still technical problems that need to be solved in the existing technology, such as poor dispersion of titanium dioxide in masterbatch, unstable structure of itself, unstable melt filtration pressure, which leads to large pigment volume concentration and FPV value of masterbatch. Summary of the Invention
[0009] To solve the above technical problems, the present invention provides a titanium dioxide for masterbatch, wherein the titanium dioxide for masterbatch is obtained by coating the surface of rutile titanium dioxide with a uniform boehmite-type hydrated aluminum oxide layer with a thickness of 5-8 nanometers and then grafting an organic surface treatment agent; the particle size of the titanium dioxide for masterbatch is 0.25-0.35 microns; The chromaticity values of the titanium dioxide include an L value (lightness) of 98.25-98.42, an a value (red-green phase) of -0.64 to -0.50, a b value (yellow-blue phase) of 1.51-1.56, and an oil absorption of 13.8-15.8 g / 100 g.
[0010] The present invention also provides a method for preparing the above-mentioned titanium dioxide for masterbatch, comprising the following steps: Step 1: taking a crude titanium dioxide product, initially crushing it, adding a pulping dispersant, fully stirring and dispersing it, and then sand-milling it to obtain a titanium dioxide slurry, and ultrasonically dispersing the titanium dioxide slurry to obtain a titanium dioxide suspension, wherein the titanium dioxide suspension includes titanium dioxide particles; Step 2: first adding an aluminum-containing compound to the titanium dioxide suspension of step 1, then adding an acid reagent for hydrolysis, gradually precipitating a boehmite-type hydrated aluminum oxide layer on the surface of the titanium dioxide particles, and then adding an acid regulator for aging to obtain a slurry after aging; During the precipitation process, the hydroxyl groups on the surface of the titanium dioxide particles and the hydroxyl groups of the boehmite-type hydrated aluminum oxide are chemically bonded, so that the boehmite-type hydrated aluminum oxide is stably attached to the surface of the titanium dioxide particles; An acid regulator is added for further aging to further precipitate a portion of the aluminum oxide that has not yet formed a precipitate onto the surface of the titanium dioxide particles, thereby obtaining a complete boehmite-type hydrated aluminum oxide layer and an aged slurry. Step 3: washing, filtering and drying the slurry in step 2 to obtain a dried solid material; Step 4: The solid material in step 3 is subjected to air flow pulverization, and an organic surface treatment agent is added to obtain the titanium dioxide for the masterbatch.
[0011] Furthermore, the crude titanium dioxide product of step 1 has a rutile titanium dioxide mass content of ≥98% and an oil absorption of ≤17 g / 100 g.
[0012] Furthermore, after the initial crushing in step 1, the crushed crude titanium dioxide is mixed with desalted water to form a crushing liquid with a crude titanium dioxide concentration of 400-600 g / L, and a pulping dispersant is added based on 0.1-0.5% of the mass of titanium dioxide in the crushing liquid.
[0013] Furthermore, the pulping dispersant in step 1 is one or more of sodium hexametaphosphate, sodium polycarboxylate, and sodium hydroxide, which is used to fully wet the titanium dioxide and prevent flocculation and sedimentation of the titanium dioxide.
[0014] Furthermore, the concentration of the beating dispersant is 15-30 g / L, and the solvent is water.
[0015] Furthermore, the equipment used for sand milling and dispersion in step 1 is a horizontal sand mill, the dispersion medium is 0.6-0.8mm zirconium dioxide beads, and the feed speed is 1-3m 3 / h, and the particle size D50 of titanium dioxide in the titanium dioxide slurry is obtained to be ≤0.4 μm.
[0016] Furthermore, in step 1, the power of ultrasonic dispersion is 300-500W, and the time is 5-20 minutes.
[0017] Furthermore, in step 2, the titanium dioxide suspension is diluted before adding the aluminum-containing compound, and the concentration of the titanium dioxide particles contained therein is diluted to 300-450 g / L.
[0018] Furthermore, the operating temperature of step 2 is 50-70°C.
[0019] Furthermore, the aluminum-containing compound in step 2 is one or more of sodium metaaluminate and aluminum sulfate.
[0020] Furthermore, in step 2, the aluminum-containing compound is a mixture with water as solvent, wherein the concentration of the solute, ie, sodium metaaluminate and / or aluminum sulfate, is 97-105 g / L in terms of alumina.
[0021] Furthermore, the acid reagent in step 2 is one or more of dilute sulfuric acid and aluminum sulfate.
[0022] Furthermore, the concentration of the dilute sulfuric acid is 97-105 g / L.
[0023] Furthermore, the mass of the aluminum-containing compound added in step 2 after conversion into aluminum oxide is 1.0-2.5% of the mass of the titanium dioxide particles.
[0024] Furthermore, in step 2, an aluminum-containing compound is added to first adjust the pH value of the titanium dioxide suspension to a range of 9-10, and then an acid reagent is added for hydrolysis. During the hydrolysis process, the pH value of the system is maintained within the range of 9-10 to ensure that boehmite-type hydrated alumina is precipitated on the surface of the titanium dioxide particles.
[0025] Furthermore, the hydrolysis time in step 2 is 90-180 min.
[0026] Furthermore, in step 2, the acid regulator adjusts the pH value of the system to within the range of 6-7 for aging.
[0027] Furthermore, the aging time in step 2 is 60-120 minutes.
[0028] Furthermore, the standard for completing the water washing in step 3 is that the conductivity of the filtrate obtained by water washing is ≤100 μs / cm, so as to remove soluble salts.
[0029] Furthermore, in step 3, the drying temperature is 100-150° C. and the drying time is 5-8 hours.
[0030] Furthermore, the intensity of the air flow crushing in step 4 is 0.7 MPa.
[0031] Furthermore, the organic surface treatment agent in step 4 is a silane coupling agent, which combines with the hydroxyl groups on the surface of the boehmite-type hydrated alumina layer to change the hydrophilicity of the titanium dioxide into lipophilicity.
[0032] Furthermore, the amount of the organic surface treatment agent added in step 4 is 0.4-1.0% of the mass of titanium dioxide in the solid material.
[0033] The present invention also provides a masterbatch, wherein the raw materials for preparing the masterbatch include the titanium dioxide for masterbatch.
[0034] Furthermore, the preparation raw materials also include polyethylene resin and antioxidant.
[0035] Furthermore, the mass ratio of the polyethylene resin, the titanium dioxide for masterbatch, and the antioxidant is (30-50): (50-70): (0.1-0.3).
[0036] Furthermore, the model of the polyethylene resin is LLDPE7042.
[0037] Furthermore, the model of the antioxidant is AT-168.
[0038] The present invention also provides a plastic, wherein the raw materials for preparing the plastic include the above-mentioned masterbatch and polyethylene particles.
[0039] Furthermore, the model of the polyethylene particles is 2426H.
[0040] Furthermore, the mass ratio of the masterbatch to the polyethylene particles is 1:(4-9).
[0041] The present invention also provides a method for preparing the above-mentioned plastic, comprising mixing masterbatch and polyethylene particles in a certain proportion and then using an injection molding device to inject the plastic; Alternatively, the masterbatch and polyethylene particles are mixed in proportion and then melt-filtered to obtain the plastic.
[0042] Furthermore, the model of the injection molding equipment is: SSF320-K5 plastic injection molding machine, the temperature is 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.70-97.92, the a value (red-green phase) was -0.56 to -0.45, and the b value (yellow-blue phase) was 2.21-2.50.
[0043] Furthermore, the plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester, and the melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added into the screw extruder, the screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C; The FPV value of the plastic in the melt filtration test was 0.052-0.067 bar / g; The calculation formula of the FPV value is: , Among them, the unit of maximum pressure and starting pressure is bar; The colorant amount is the mass of titanium dioxide, in g.
[0044] The beneficial effects of the present invention are: 1. The present invention provides a titanium dioxide for masterbatch. The titanium dioxide for masterbatch is obtained by coating the surface of rutile titanium dioxide with a uniform boehmite-type hydrated alumina layer having a thickness of 5-8 nanometers and then grafting an organic surface treatment agent. When used in masterbatch, the titanium dioxide can effectively reduce the FPV value (melt filtration pressure value) of the masterbatch during the plastic preparation process. A lower FPV value indicates better melt filtration stability and better dispersion of the titanium dioxide in the masterbatch. The better the dispersion, the more uniform the film formation or injection molding of the plastic product, effectively improving product quality and reducing production costs. The titanium dioxide prepared by the present invention has the advantages of good dispersibility and stable plastic melt filtration performance. It effectively improves the shortcomings of titanium dioxide in the masterbatch production process, such as poor dispersibility and unstable melt filtration pressure, and can meet the production needs of high-end masterbatches. The preparation process is simple and is easy to promote and use. 2. The preparation method of the present invention achieves a melt FPV value in masterbatch applications that is lower than that of domestic products LR108, R-666, and SR240, demonstrating that the titanium dioxide prepared by the present invention has good filtration stability. Although the performance of the titanium dioxide prepared is slightly inferior to that of the foreign product R-104, the sulfuric acid method of the present invention significantly reduces the cost for downstream customers compared to the product prepared by the chlorination method of the prior art for preparing R-104, facilitating its widespread promotion and use. 3. The present invention coats a boehmite-type hydrated alumina layer on the surface of titanium dioxide. Compared with the amorphous aluminum hydroxide with unstable coating performance in the prior art, the present invention coats the surface of titanium dioxide with a boehmite-type hydrated alumina with a specific thickness and structure. Due to its special uniform cubic structure, it has a higher zero-point charge and interfacial free energy, larger porosity and specific surface area, so that the titanium dioxide prepared by the present invention can have good dispersibility after mixing with polyethylene materials, and the prepared masterbatch and the plastic products used at the lower end have higher performance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a scanning electron microscope image of the titanium dioxide prepared in accordance with an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of titanium dioxide purchased for comparative example; Figure 3This is a graph showing the FPV value test results of the plastic in Example 13 of the present invention in a melt filtration test; Figure 4 This is a graph showing the FPV value test results of the plastic in Example 14 of the present invention in a melt filtration test; Figure 5 This is a graph showing the FPV value test results of the plastic in Example 15 of the present invention in a melt filtration test; Figure 6 This is a graph showing the FPV value test results of the plastic in Example 16 of the present invention in a melt filtration test; Figure 7 This is a graph showing the FPV value test results of the plastic of Comparative Example 13 of the present invention in a melt filtration test; Figure 8 This is a graph showing the FPV value test results of the plastic of Comparative Example 14 of the present invention in a melt filtration test; Figure 9 This is a graph showing the FPV value test results of the plastic of Comparative Example 15 of the present invention in a melt filtration test; Figure 10 This is a graph showing the FPV value test results of the plastic of Comparative Example 16 of the present invention in the melt filtration test. DETAILED DESCRIPTION
[0046] Examples 1-4 are titanium dioxide for masterbatch of the present invention and preparation methods thereof; Examples 5-8 are masterbatches prepared using the titanium dioxide in Examples 1-4; Examples 9-12 are plastics prepared by injection molding using the masterbatches in Examples 5-8; Examples 13-16 are plastics prepared by melt filtration tests using the masterbatches in Examples 5-8.
[0047] Example 1 This embodiment provides a titanium dioxide for masterbatch and a preparation method thereof, the preparation method comprising the following steps: Step 1: Take the crude titanium dioxide, crush it initially, and mix the crushed crude titanium dioxide with desalted water to form a crushing liquid with a concentration of 600g / L of crude titanium dioxide. Add a pulping dispersant, sodium hexametaphosphate, based on 0.3% of the mass of titanium dioxide in the crushing liquid. After fully stirring and dispersing, use a horizontal sand mill to grind and disperse. The dispersing medium is 0.6mm zirconium dioxide beads. The feed speed is 2m 3 / h, obtaining a titanium dioxide slurry with a particle size D50≤0.4 μm, obtaining a titanium dioxide slurry, and ultrasonically dispersing the titanium dioxide slurry at a power of 300 W for 10 min to obtain a titanium dioxide suspension, wherein the titanium dioxide suspension includes titanium dioxide particles; Among them, the crude titanium dioxide meets the requirements of rutile titanium dioxide mass content ≥98% and oil absorption ≤17g / 100g; Step 2: before adding the aluminum-containing compound, the titanium dioxide suspension is diluted to dilute the concentration of the titanium dioxide particles contained therein to 300 g / L, the pH value is adjusted to 9.0, steam is introduced to heat it and the temperature is maintained at 60° C., and the aluminum-containing compound is first added to the diluted titanium dioxide suspension, wherein the aluminum-containing compound is a mixture with water as a solvent, wherein the solute is sodium aluminate and aluminum sulfate in a mass ratio of 1.5:1, and the mass of the sodium aluminate and aluminum sulfate added at the same time is converted into aluminum oxide, which is 2.0% of the mass of the titanium dioxide particles, thereby generating a precipitate, and then adding an acid reagent, dilute sulfuric acid, for hydrolysis, the hydrolysis time is 90 minutes, and a boehmite-type hydrated aluminum oxide layer is gradually precipitated on the surface of the titanium dioxide particles. After the precipitation is completed, dilute sulfuric acid, an acid regulator, is added for aging, and the pH value of the system is adjusted to 6. The aging time is 60 minutes, and a slurry is obtained after aging; Step 3: washing, filtering and drying the slurry in step 2, wherein the criterion for completion of washing is that the conductivity of the filtrate obtained by washing is ≤100 μs / cm, and the drying temperature is 100° C. and the drying time is 5 h to obtain a dried solid material; Step 4: The solid material of step 3 is subjected to air flow pulverization at an intensity of 0.7 MPa, and an organic surface treatment agent, a silane coupling agent, is added at the same time in an amount of 0.4% of the mass of titanium dioxide in the solid material to obtain the titanium dioxide for the masterbatch.
[0048] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 98.37, a value (red-green phase) is -0.64, b value (yellow-blue phase) is 1.53, and oil absorption is 15.3 g / 100 g. Figure 1 As shown, the titanium dioxide prepared in this example was subjected to scanning electron microscopy.
[0049] Example 2 This embodiment provides a titanium dioxide for masterbatch and a preparation method thereof, the preparation method comprising the following steps: Step 1: Take the crude titanium dioxide, crush it initially, and mix the crushed crude titanium dioxide with desalted water to form a crushing liquid with a concentration of 400g / L of crude titanium dioxide. Add a pulping dispersant, sodium polycarboxylate, based on 0.5% of the mass of titanium dioxide in the crushing liquid. After fully stirring and dispersing, use a horizontal sand mill to grind and disperse. The dispersing medium is 0.6mm zirconium dioxide beads. The feed speed is 3m 3 / h, obtaining a titanium dioxide slurry with a particle size D50≤0.4 μm, obtaining a titanium dioxide slurry, and ultrasonically dispersing the titanium dioxide slurry at a power of 500 W for 5 minutes to obtain a titanium dioxide suspension, wherein the titanium dioxide suspension includes titanium dioxide particles; Among them, the crude titanium dioxide meets the requirements of rutile titanium dioxide mass content ≥98% and oil absorption ≤17g / 100g; Step 2: before adding the aluminum-containing compound, the titanium dioxide suspension is diluted to dilute the concentration of the titanium dioxide particles contained therein to 350 g / L, the pH value is adjusted to 9.5, steam is introduced to heat it and the temperature is maintained at 50° C., and the aluminum-containing compound is first added to the diluted titanium dioxide suspension, wherein the aluminum-containing compound is a mixture with water as a solvent, wherein the solute is sodium aluminate and aluminum sulfate in a mass ratio of 1:1, and the mass of the sodium aluminate and aluminum sulfate added at the same time is converted into aluminum oxide and is 1.0% of the mass of the titanium dioxide particles, thereby generating a precipitate, and then adding an acid reagent, dilute sulfuric acid, for hydrolysis, the hydrolysis time is 120 minutes, and a boehmite-type hydrated aluminum oxide layer is gradually precipitated on the surface of the titanium dioxide particles. After the precipitation is completed, dilute sulfuric acid, an acid regulator, is added for aging, and the pH value of the system is adjusted to 6.5. The aging time is 90 minutes, and a slurry is obtained after aging; Step 3: washing, filtering and drying the slurry in step 2, wherein the standard for completion of washing is that the conductivity of the filtrate obtained by washing is ≤100 μs / cm, and the drying temperature is 150° C. and the time is 6 hours to obtain a dried solid material; Step 4: The solid material of step 3 is subjected to air flow crushing at an intensity of 0.7 MPa, and an organic surface treatment agent, a silane coupling agent, is added at the same time in an amount of 0.5% of the mass of titanium dioxide in the solid material to obtain the titanium dioxide for the masterbatch.
[0050] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 98.25, a value (red-green phase) is -0.53, b value (yellow-blue phase) is 1.54, and oil absorption is 13.8 g / 100 g. Figure 1 As shown, the titanium dioxide prepared in this example was subjected to scanning electron microscopy.
[0051] Example 3 This embodiment provides a titanium dioxide for masterbatch and a preparation method thereof, the preparation method comprising the following steps: Step 1: Take the crude titanium dioxide, crush it initially, and mix the crushed crude titanium dioxide with desalted water to form a crushing liquid with a concentration of 500 g / L of crude titanium dioxide. Add sodium hexametaphosphate and sodium hydroxide in a mass ratio of 2:3 to the crushing liquid, based on 0.1% of the mass of titanium dioxide in the crushing liquid. After fully stirring and dispersing, use a horizontal sand mill to grind and disperse. The dispersing medium is 0.8 mm zirconium dioxide beads, and the feed speed is 1 m 3 / h, obtaining a titanium dioxide slurry with a particle size D50≤0.4 μm, obtaining a titanium dioxide slurry, and ultrasonically dispersing the titanium dioxide slurry at a power of 300 W for 20 min to obtain a titanium dioxide suspension, wherein the titanium dioxide suspension includes titanium dioxide particles; Among them, the crude titanium dioxide meets the requirements of rutile titanium dioxide mass content ≥98% and oil absorption ≤17g / 100g; Step 2: before adding the aluminum-containing compound, the titanium dioxide suspension is diluted to dilute the concentration of the titanium dioxide particles contained therein to 400 g / L, the pH value is adjusted to 10.0, steam is introduced to heat it and the temperature is maintained at 60° C., and the aluminum-containing compound is first added to the diluted titanium dioxide suspension, wherein the aluminum-containing compound is a mixture with water as a solvent, wherein the solute is sodium aluminate and aluminum sulfate with a mass ratio of 1.5:1, and the mass of the sodium aluminate and aluminum sulfate added at the same time is converted into aluminum oxide, which is 2.5% of the mass of the titanium dioxide particles, thereby generating a precipitate, and then adding an acid reagent, dilute sulfuric acid, for hydrolysis. The hydrolysis time is 120 minutes, and a boehmite-type hydrated aluminum oxide layer is gradually precipitated on the surface of the titanium dioxide particles. After the precipitation is completed, dilute sulfuric acid, an acid regulator, is added for aging, and the pH value of the system is adjusted to 6.5. The aging time is 90 minutes, and a slurry is obtained after aging; Step 3: washing, filtering and drying the slurry in step 2, wherein the criterion for completion of washing is that the conductivity of the filtrate obtained by washing is ≤100 μs / cm, and the drying temperature is 100° C. and the drying time is 8 hours to obtain a dried solid material; Step 4: The solid material of step 3 is subjected to air flow crushing at an intensity of 0.7 MPa, and an organic surface treatment agent, a silane coupling agent, is added at the same time in an amount of 0.7% of the mass of titanium dioxide in the solid material to obtain the titanium dioxide for the masterbatch.
[0052] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 98.42, a value (red-green phase) is -0.50, b value (yellow-blue phase) is 1.56, and oil absorption is 15.8g / 100g. Figure 1 As shown, the titanium dioxide prepared in this example was subjected to scanning electron microscopy.
[0053] Example 4 This embodiment provides a titanium dioxide for masterbatch and a preparation method thereof, the preparation method comprising the following steps: Step 1: Take the crude titanium dioxide, crush it initially, and mix the crushed crude titanium dioxide with desalted water to form a crushing liquid with a concentration of 600g / L of crude titanium dioxide. Add a pulping dispersant, sodium polycarboxylate, based on 0.4% of the mass of titanium dioxide in the crushing liquid. After fully stirring and dispersing, use a horizontal sand mill to grind and disperse. The dispersing medium is 0.8mm zirconium dioxide beads. The feed speed is 1m 3 / h, obtaining a titanium dioxide slurry with a particle size D50≤0.4 μm, obtaining a titanium dioxide slurry, and ultrasonically dispersing the titanium dioxide slurry at a power of 500 W for 5 minutes to obtain a titanium dioxide suspension, wherein the titanium dioxide suspension includes titanium dioxide particles; Among them, the crude titanium dioxide meets the requirements of rutile titanium dioxide mass content ≥98% and oil absorption ≤17g / 100g; Step 2: before adding the aluminum-containing compound, the titanium dioxide suspension is diluted to dilute the concentration of the titanium dioxide particles contained therein to 450 g / L, the pH value is adjusted to 9.0, steam is introduced to heat it and the temperature is maintained at 70° C., and the aluminum-containing compound is first added to the diluted titanium dioxide suspension, wherein the aluminum-containing compound is a mixture with water as a solvent, wherein the solute is sodium aluminate and aluminum sulfate in a mass ratio of 1:1, and the mass of the sodium aluminate and aluminum sulfate added at the same time is converted into aluminum oxide and is 1.5% of the mass of the titanium dioxide particles, thereby generating a precipitate, and then adding an acid reagent, dilute sulfuric acid, for hydrolysis, the hydrolysis time is 180 minutes, and a boehmite-type hydrated aluminum oxide layer is gradually precipitated on the surface of the titanium dioxide particles. After the precipitation is completed, dilute sulfuric acid, an acid regulator, is added for aging, and the pH value of the system is adjusted to 7.0. The aging time is 120 minutes, and a slurry is obtained after aging; Step 3: washing, filtering and drying the slurry in step 2, wherein the criterion for completion of washing is that the conductivity of the filtrate obtained by washing is ≤100 μs / cm, and the drying temperature is 150° C. for 5 hours to obtain a dried solid material; Step 4: The solid material of step 3 is subjected to air flow crushing at an intensity of 0.7 MPa, and an organic surface treatment agent, a silane coupling agent, is added at the same time in an amount of 1.0% of the mass of titanium dioxide in the solid material to obtain the titanium dioxide for the masterbatch.
[0054] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 98.29, a value (red-green phase) is -0.61, b value (yellow-blue phase) is 1.51, and oil absorption is 14.2 g / 100 g. Figure 1 As shown, the titanium dioxide prepared in this example was subjected to scanning electron microscopy.
[0055] Example 5 This embodiment provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch of Example 1, and an antioxidant (AT-168). The masterbatch of this embodiment is prepared using conventional methods in the prior art.
[0056] Example 6 This embodiment provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch of Example 2, and an antioxidant (AT-168). The masterbatch of this embodiment is prepared using conventional methods in the prior art.
[0057] Example 7 This embodiment provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch of Example 3, and an antioxidant (AT-168). The masterbatch of this embodiment is prepared using conventional methods in the prior art.
[0058] Example 8 This embodiment provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch of Example 4, and an antioxidant (AT-168). The masterbatch of this embodiment is prepared using conventional methods in the prior art.
[0059] Example 9 This embodiment provides a plastic, wherein the raw materials for preparing the plastic are 10 g of the masterbatch of Example 5 and 90 g of polyethylene particles (2426H).
[0060] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.70, the a value (red-green phase) was -0.45, and the b value (yellow-blue phase) was 2.50.
[0061] Example 10 This embodiment provides a plastic, wherein the raw materials for preparing the plastic are 10 g of the masterbatch of Example 6 and 90 g of polyethylene particles (2426H).
[0062] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.77, the a value (red-green phase) was -0.50, and the b value (yellow-blue phase) was 2.21.
[0063] Example 11 This embodiment provides a plastic, wherein the raw materials for preparing the plastic are 10 g of the masterbatch of Example 7 and 90 g of polyethylene particles (2426H).
[0064] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.92, the a value (red-green phase) was -0.54, and the b value (yellow-blue phase) was 2.31.
[0065] Example 12 This embodiment provides a plastic, wherein the raw materials for preparing the plastic are 10 g of the masterbatch of Example 8 and 90 g of polyethylene particles (2426H).
[0066] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.59, the a value (red-green phase) was -0.56, and the b value (yellow-blue phase) was 2.40.
[0067] Example 13 This embodiment also provides a plastic (No. SL 1), which is obtained by mixing the masterbatch of Example 5 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0068] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.065 bar / g; The calculation formula of the FPV value is: , In this embodiment, the maximum pressure is 108.144 bar and the starting pressure is 100.309 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 3 shown.
[0069] Example 14 This embodiment also provides a plastic (No. SL 2), which is obtained by mixing the masterbatch of Example 6 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0070] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.067 bar / g; The calculation formula of the FPV value is: , In this embodiment, the maximum pressure is 107.367 bar and the starting pressure is 99.379 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 4 shown.
[0071] Example 15 This embodiment also provides a plastic (No. SL 3), which is obtained by mixing the masterbatch of Example 7 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0072] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.052 bar / g; The calculation formula of the FPV value is: , In this embodiment, the maximum pressure is 105.340 bar and the starting pressure is 99.096 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 5 shown.
[0073] Example 16 This embodiment also provides a plastic (No. SL 4), which is obtained by mixing the masterbatch of Example 8 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0074] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.057 bar / g; The calculation formula of the FPV value is: , In this embodiment, the maximum pressure is 102.760 bar and the starting pressure is 95.938 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 6 shown.
[0075] Comparative Example 1 The commercially available model is LR-108 domestic masterbatch titanium dioxide.
[0076] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 98.27, a value (red-green phase) is -0.44, b value (yellow-blue phase) is 1.59, and oil absorption is 14.9 g / 100 g. Figure 2 As shown, the masterbatch purchased in this comparative example was tested by scanning electron microscopy.
[0077] Comparative Example 2 The commercially available model is R-666 domestic masterbatch titanium dioxide.
[0078] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 98.53, a value (red-green phase) is -0.47, b value (yellow-blue phase) is 1.41, and oil absorption is 14.1 g / 100 g. Figure 2 As shown, the masterbatch purchased in this comparative example was tested by scanning electron microscopy.
[0079] Comparative Example 3 The commercially available model is SR240 domestic masterbatch titanium dioxide.
[0080] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 97.72, a value (red-green phase) is -0.54, b value (yellow-blue phase) is 1.47, and oil absorption is 15.2 g / 100 g. Figure 2 As shown, the masterbatch purchased in this comparative example was tested by scanning electron microscopy.
[0081] Comparative Example 4 The commercially available model is R-104 titanium dioxide for foreign masterbatch.
[0082] The chromaticity values of the titanium dioxide are as follows: L value (lightness) is 99.01, a value (red-green phase) is -0.45, b value (yellow-blue phase) is 1.23, and oil absorption is 12.5g / 100g. Figure 2 As shown, the masterbatch purchased in this comparative example was tested by scanning electron microscopy.
[0083] Will Figure 1 and Figure 2 By comparison, it can be clearly seen that the surface of the titanium dioxide prepared in the present invention is coated with a uniform boehmite-type hydrated aluminum oxide layer.
[0084] Comparative Example 5 This comparative example provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch in comparative example 1, and an antioxidant (AT-168).
[0085] Comparative Example 6 This comparative example provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch of comparative example 2, and an antioxidant (AT-168).
[0086] Comparative Example 7 This comparative example provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch of comparative example 3, and an antioxidant (AT-168).
[0087] Comparative Example 8 This comparative example provides a masterbatch, wherein the raw materials for preparing the masterbatch include polyethylene resin (LLDPE7042 powder) in a mass ratio of 40:60:0.2, titanium dioxide for the masterbatch in comparative example 4, and an antioxidant (AT-168).
[0088] Comparative Example 9 This comparative example provides a plastic, and the raw materials for preparing the plastic are 10g of the masterbatch of comparative example 5 and 90g of polyethylene particles (2426H).
[0089] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.67, the a value (red-green phase) was -0.46, and the b value (yellow-blue phase) was 2.34.
[0090] Comparative Example 10 This comparative example provides a plastic, and the raw materials for preparing the plastic are 10g of comparative example 6 color masterbatch and 90g of polyethylene particles (2426H).
[0091] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 97.34, the a value (red-green phase) was -0.21, and the b value (yellow-blue phase) was 2.35.
[0092] Comparative Example 11 This comparative example provides a plastic, and the raw materials for preparing the plastic are 10g of comparative example 7 color masterbatch and 90g of polyethylene particles (2426H).
[0093] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 96.96, the a value (red-green phase) was -0.13, and the b value (yellow-blue phase) was 2.37.
[0094] Comparative Example 12 This comparative example provides a plastic, and the raw materials for preparing the plastic are 10g of comparative example 8 masterbatch and 90g of polyethylene particles (2426H).
[0095] The masterbatch and polyethylene particles are mixed in proportion and then injected into a sample of the plastic using an injection molding machine; wherein the injection molding machine is an SSF320-K5 plastic injection molding machine at a temperature of 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value (lightness) was 98.02, the a value (red-green phase) was -0.48, and the b value (yellow-blue phase) was 2.28.
[0096] Comparative Example 13 This comparative example also provides a plastic (No. LR-108), which is obtained by mixing the color masterbatch of comparative example 4 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0097] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.099 bar / g; The calculation formula of the FPV value is: , Among them, in this comparative example, the maximum pressure is 117.876 bar and the starting pressure is 105.976 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 7 shown.
[0098] Comparative Example 14 This comparative example also provides a plastic (No. R-666), which is obtained by mixing the masterbatch of comparative example 5 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0099] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.070 bar / g; The calculation formula of the FPV value is: , Among them, in this comparative example, the maximum pressure is 104.845 bar and the starting pressure is 96.410 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 8 shown.
[0100] Comparative Example 15 This comparative example also provides a plastic, which is obtained by mixing the color masterbatch of comparative example 7 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration to obtain the plastic (No. SR240).
[0101] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.154 bar / g; The calculation formula of the FPV value is: , Among them, in this comparative example, the maximum pressure is 118.654 bar and the starting pressure is 100.133 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 9 shown.
[0102] Comparative Example 16 This comparative example also provides a plastic (No. R-104), which is obtained by mixing the masterbatch of comparative example 8 and polyethylene particles (2426H) in a mass ratio of 1:4, and then performing melt filtration.
[0103] The plastic obtained by melt filtration was subjected to a filter pressure value test: the filter pressure value test equipment model is: BP-8186-B filterability tester. The melt filtration test is as follows: the masterbatch and polyethylene particles are mixed according to the ratio and then added to the screw extruder. The screw speed is 40 rpm, the mesh size of the filter is 1400 mesh, and the filtration temperature is 190°C. The FPV value of the plastic in the melt filtration test was 0.034 bar / g; The calculation formula of the FPV value is: , Among them, in this comparative example, the maximum pressure is 97.505 bar and the starting pressure is 93.394 bar; The coloring amount is the mass of titanium dioxide, the unit is 120g, the test results are as follows Figure 10 shown.
[0104] The performance of the titanium dioxide in Examples 1-4 and Comparative Examples 1-4 was compared, and the results are shown in Table 1: Table 1 Comparison of the properties of titanium dioxide in Examples 1-4 and Comparative Examples 1-4
[0105] The properties of the plastics prepared in Examples 9-12 and Comparative Examples 9-12 were compared, and the results are shown in Table 2: Table 2 Comparison of properties of plastics prepared in Examples 9-12 and Comparative Examples 9-12
[0106] The properties of the plastics prepared in Examples 13-16 and Comparative Examples 13-16 were compared, and the results are shown in Table 3: Table 3 Comparison of properties of plastics prepared in Examples 13-16 and Comparative Examples 13-16
[0107] From the above comparison, it can be seen that the titanium dioxide prepared by the present invention is used in masterbatch, which can effectively reduce the FPV value (melt filtration pressure value) of the masterbatch in the process of preparing plastics. The smaller the FPV value, the better the melt filtration stability, the better the dispersion of titanium dioxide in the masterbatch, and the better the dispersion, the more uniform the film formation or injection molding of the plastic product, which effectively improves product quality and reduces production costs.
[0108] It should be understood that the present invention is not limited to what has been described above and shown in the accompanying drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A titanium dioxide for masterbatch, characterized in that: The titanium dioxide for masterbatch is obtained by coating the surface of rutile titanium dioxide with a uniform boehmite-type hydrated aluminum oxide layer with a thickness of 5-8 nanometers and then grafting an organic surface treatment agent; the particle size of the titanium dioxide for masterbatch is 0.25-0.35 microns; Among the chromaticity values of the titanium dioxide, the L value is 98.25-98.42, the a value is -0.64 to -0.50, the b value is 1.51-1.56, and the oil absorption is 13.8-15.8 g / 100 g.
2. A method for preparing titanium dioxide for masterbatch according to claim 1, characterized in that: The steps include: Step 1, taking a crude titanium dioxide product, preliminarily crushing it, adding a pulping dispersant, fully stirring and pulping it, and then sand-milling it to obtain a titanium dioxide slurry, and ultrasonically dispersing the titanium dioxide slurry to obtain a titanium dioxide suspension, wherein the titanium dioxide suspension includes titanium dioxide particles; Step 2, first add an aluminum compound to the titanium dioxide suspension of step 1, then add an acid reagent for hydrolysis, gradually precipitate on the surface of the titanium dioxide particles to form a boehmite-type hydrated aluminum oxide layer, and then add an acid regulator for aging to obtain a slurry after aging; Step 3, washing, filtering and drying the slurry in step 2 to obtain a dried solid material; Step 4: air flow pulverize the solid material in step 3, and add an organic surface treatment agent to obtain the titanium dioxide for masterbatch.
3. The method for preparing titanium dioxide for masterbatch according to claim 2, characterized in that: In step 1, the pulping dispersant is one or more of sodium hexametaphosphate, sodium polycarboxylate, and sodium hydroxide.
4. The method for preparing titanium dioxide for masterbatch according to claim 2, characterized in that: In step 2, the aluminum-containing compound is one or more of sodium aluminate and aluminum sulfate.
5. The method for preparing titanium dioxide for masterbatch according to claim 2, characterized in that: In step 4, the organic surface treatment agent is a silane coupling agent.
6. A masterbatch, characterized in that: The raw materials for preparing the masterbatch include the titanium dioxide for masterbatch according to claim 1.
7. A plastic, characterized in that: The raw materials for preparing the plastic include the masterbatch according to claim 6 and polyethylene particles.
8. A method for preparing the plastic according to claim 7, characterized in that: Mixing the masterbatch and the polyethylene particles in proportion and then using an injection molding device to inject the plastic; Alternatively, the masterbatch and polyethylene particles are mixed in proportion and then melt-filtered to obtain the plastic.
9. The method for preparing plastic according to claim 8, characterized in that: The model of the injection molding equipment is: SSF320-K5 plastic injection molding machine, the temperature is 190°C; The plastic obtained by injection molding was tested: in the chromaticity values of the plastic, the L value was 97.70-97.92, the a value was -0.56 to -0.45, and the b value was 2.21-2.
50.
10. The method for preparing plastic according to claim 8, characterized in that: The plastic obtained by melt filtration is tested for filter pressure value: the model of the filter pressure value test equipment is: BP-8186-B filterability tester, and the melt filtration test is to add the masterbatch and polyethylene particles into the screw extruder after mixing them according to the ratio, the screw speed is 40rpm, the mesh number of the filter is 1400 mesh, and the filtration temperature is 190°C; The FPV value of the plastic in the melt filtration test is 0.052-0.067 bar / g; The calculation formula of the FPV value is: , Among them, the unit of maximum pressure and starting pressure is bar; The coloring amount is the mass of titanium dioxide, in g.
Citation Information
Patent Citations
Preparation method of special titanium dioxide with high dispersibility and low oil absorption
CN117024992A
Cited By
White master batch for high-stiffness and high-heat-resistance BOPP (biaxially-oriented polypropylene) film as well as preparation method and application of white master batch
CN121182070A
